2023
DOI: 10.1186/s13287-023-03236-4
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic therapeutic effects of intracerebral transplantation of human modified bone marrow-derived stromal cells (SB623) and voluntary exercise with running wheel in a rat model of ischemic stroke

Abstract: Background Mesenchymal stromal cell (MSC) transplantation therapy is a promising therapy for stroke patients. In parallel, rehabilitation with physical exercise could ameliorate stroke-induced neurological impairment. In this study, we aimed to clarify whether combination therapy of intracerebral transplantation of human modified bone marrow-derived MSCs, SB623 cells, and voluntary exercise with running wheel (RW) could exert synergistic therapeutic effects on a rat model of ischemic stroke. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Recently, using a stroke animal model, a positive influence of voluntary exercise on mesenchymal stromal cell (MSC) transplantation therapy was demonstrated. Yabuno et al (2023) found that neurological deficits in rats inflicted with transient middle cerebral artery occlusion were significantly reversed after a combination of voluntary exercise (wheel running) and intracerebral transplantation of human modified bone marrow-derived MSCs [ 48 ]. Importantly, endogenous neurogenesis in the subventricular zone (SVZ) and DG, and mRNA levels of VEGF and BDNF, were also upregulated by mice undergoing the combination of exercise and MSC transplantation compared to those in single therapy or without therapy [ 48 ].…”
Section: Roles Of Bdnf/trkb System In Cns Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using a stroke animal model, a positive influence of voluntary exercise on mesenchymal stromal cell (MSC) transplantation therapy was demonstrated. Yabuno et al (2023) found that neurological deficits in rats inflicted with transient middle cerebral artery occlusion were significantly reversed after a combination of voluntary exercise (wheel running) and intracerebral transplantation of human modified bone marrow-derived MSCs [ 48 ]. Importantly, endogenous neurogenesis in the subventricular zone (SVZ) and DG, and mRNA levels of VEGF and BDNF, were also upregulated by mice undergoing the combination of exercise and MSC transplantation compared to those in single therapy or without therapy [ 48 ].…”
Section: Roles Of Bdnf/trkb System In Cns Neuronsmentioning
confidence: 99%
“…Yabuno et al (2023) found that neurological deficits in rats inflicted with transient middle cerebral artery occlusion were significantly reversed after a combination of voluntary exercise (wheel running) and intracerebral transplantation of human modified bone marrow-derived MSCs [ 48 ]. Importantly, endogenous neurogenesis in the subventricular zone (SVZ) and DG, and mRNA levels of VEGF and BDNF, were also upregulated by mice undergoing the combination of exercise and MSC transplantation compared to those in single therapy or without therapy [ 48 ]. In addition, using an animal model of Parkinson’s disease (PD), which is also one of the most common neurodegenerative diseases, the upregulation of BDNF and an increase in neurogenesis following exercise was demonstrated.…”
Section: Roles Of Bdnf/trkb System In Cns Neuronsmentioning
confidence: 99%
“…Indeed, voluntary exercise combined with the IC transplantation of human BMMSCs may improve gross neurological but not sensorimotor recovery at postoperative Day 14 in a rat transient MCAO model. 43 The underlying therapeutic mechanisms put forward include the synergistic effects on the attenuation of infarct size, angiogenesis, as well as BDNF-and VEGF-mediated neurogenesis. The low survival (<0.05%) of the transplanted cells at Day 3, however, likely as a result of technical issues, might partly explain the overlapping/limited combinatorial effect on the behavioral outcomes.…”
Section: Behavioral Effects Of Combining the Stereotactic Transplanta...mentioning
confidence: 99%
“…It is imperative that the increase in endogenous NSPCs after cell‐based therapy must be followed up with not only an increased training but also an appropriate rehabilitation modality that would allow the immature endogenous and exogenous cells to properly mature and effectively integrate with the host tissue. Voluntary exercise, forced physical training, and EE have all been shown to improve motor function by increasing BDNF and neurogenesis, which is one of the main driving forces underlying stroke recovery 24,25,43,61 . However, behavioral task specificity and integration need to be more widely incorporated in experimental rehabilitation strategies to achieve better functional outcomes in stroke animals 39 …”
Section: How To Maximize Therapeutic Effect In a Combined Cell‐based ...mentioning
confidence: 99%
See 1 more Smart Citation